Stomaching uncertainty: Relationships among intolerance of uncertainty, eating disorder pathology, and comorbid emotional symptoms - Renjan, V.; McEvoy, Peter; Handley, A.; Fursland, A. (Pergamon, 2015)
Intolerance of uncertainty (IU) is proposed to be a transdiagnostic vulnerability factor for various emotional disorders. There is robust evidence for the role of IU in anxiety and depressive disorders, but a paucity of evidence in eating disorders (ED). This study evaluated the factorial validity, internal consistency, and convergent validity of the Intolerance of Uncertainty Scale-Short Form (IUS-12; Carleton, Norton, & Asmundson, 2007), and examined whether IU is associated with ED pathology and comorbid emotional symptoms, in a clinical sample with EDs (N = 134). A unitary factor solution provided the best fit. The IUS-12 showed excellent internal consistency, and good convergent validity. IU had an indirect effect on dietary restraint, purging, and emotional symptoms via overvaluation of eating, weight, and shape. The indirect effect was not significant for bingeing. Findings provide partial support for the notion that IU is a vulnerability factor for ED pathology and support the notion that IU is a transdiagnostic vulnerability factor for emotional symptoms. Limitations, research implications, and future directions for research are discussed.